Estrategias de comunicación y marketing de marcas de lujo y fast fashion durante la crisis del COVID-19 (Ensayos) - Crespo Pereira, Verónica (2022)
This article provides a state of the art on the communication and marketing strategies that fashion brands have carried out during the period of COVID-19 confinement. For this purpose, a bibliographic review of articles that meet the aforementioned thematic and methodological criteria (content analysis) has been carried out. The results show a similarity of strategies and actions carried out by 10 luxury brands, as well as by three fast fashion brands at the beginning of COVID-19. Although the COVID-19 crisis prevents brand fashion brands from adopting product promotional strategies, it does allow work on the reputation and brand image among its different stakeholders. The pandemic creates a favorable context to show the most humane and supportive facet of brands. The results reveal that communication strategies look for the creation of brand affinity and community feelings through valuable and entertaining social media content. On the other hand, social platforms informed employees and society about the work of brands to maintain templates and ensure health safety at work. The campaigns for the donation of material and financial resources allow, in turn, to make visible, through the media, the brand’s commitment to the community.